Eksistensi Home Industri Kerajinan Anyaman Bambu di Heuleut Leuwimunding Majalengka di Era Revolusi Industri 4.0 - Barnawi Barnawi (Etos : Jurnal Pengabdian Masyarakat, 2019)
This research is focused on the home industry of woven bamboo crafts in the village of Heuleut Leuwimunding Majalengka in 2019. The aspect studied is the objective conditions of the existence of woven bamboo crafts in the midst of the industrial revolution 4.0. This study aims to describe the existence of the bamboo handicraft home industry in the village of Heuleut Leuwimunding, Majalengka in 2019 in the midst of the industrial revolution 4.0. This research is a qualitative research. This type of research was chosen because qualitative research is able to provide descriptive data in the form of written or spoken words from the behavior of the people being observed. So that in researching "The Existence of Home Industry Bamboo Matting, Heuleut Leuwimunding Majalengka Village in the Industrial Revolution Era 4.0" qualitative research is needed in order to obtain descriptive data. Based on the research findings and analysis of the research findings, the existence of the bamboo woven handicraft home industry in the village of Heuleut Leuwidinding Majalengka in the era of the industrial revolution 4.0 can be concluded that the production factor is still traditional in both the aspects of raw material procurement and product design. From the aspect of acceptability, the village of Heuleut Leuwidinding Majalengka is relatively easy to reach so that it does not complicate direct marketing. In selling products, the craftsmen do not market directly but there are collectors who will market the products. In the new marketing using traditional marketing, not yet using online sales. The government regulations have not been used by craftsmen both in the aspects of capital and guidance. In general, the existence of the bamboo woven handicraft home industry in the village of Heuleut Leuwidinding Majalengka in the era of the industrial revolution 4.0 will be eroded by other parties who will adopt the bamboo woven home industry using machines and with more sophisticated designs (computing). Furthermore, the bamboo woven handicraft home industry in the village of Heuleut Leuwidinding Majalengka in the era of the industrial revolution 4.0 will reduce the craftsmen's economy because it is limited to producing products traditionally without any product development, results, and marketing. Abstrak Penelitian ini difokuskan pada home industry kerajinan anyaman bambu di desa Heuleut Leuwimunding Majalengka Tahun 2019. Aspek yang dikaji adalah kondisi objektif tentang eksistensi kerajinan anyaman bambu di tengah revolusi industri 4.0. Penelitian ini bertujuan untuk mendeskripsikan eksistensi home industry kerajinan bambu di desa Heuleut Leuwimunding Majalengka Tahun 2019 di tengah revolusi industri 4.0. Penelitian ini merupakan penelitian kualitatif. Jenis penelitian ini dipilih karena penelitian kualitatif mampu memberikan data deskriptif berupa kata-kata tertulis atau lisan dari perilaku orang yang diamati. Sehingga dalam meneliti “Eksistensi Home Industri Anyaman Bambu Desa Heuleut Leuwimunding Majalengka di Era Revolusi Industri 4.0 “penelitian kualitatif diperlukan agar mendapatkan data-data deskriptif. Bersadarkan temuan penelitian dan analisis hasil temuan penelitian maka eksistensi home industry kerajinan anyaman bambu desa Heuleut Leuwidinding Majalengka di era revolusi industri 4.0 dapat disimpulkan faktor produksi masih bercorak tradisional baik dari aspek pengadaan bahan baku maupun desain hasil produk. Dari aspek aksepbilitas desa Heuleut Leuwidinding Majalengka relatif mudah dijangkau sehingga tidak menyulitkan dalam pemasaran langsung. Dalam penjualan produk, pengrajin tidak memasarkan secara langsung tetapi ada pengepul yang akan memasarkan produk. Dalam pemasaran baru menggunakan pemasaran secara tradisional, belum menggunakan penjualan online. Adapun regulasi pemerintah belum dimanfaatkan oleh pengrajin baik pada aspek modal maupun pembinaan. Secara umum eksistensi home industry kerajinan anyaman bambu desa Heuleut Leuwidinding Majalengka di era revolusi industri 4.0 akan tergerus oleh pihak lain yang akan mengadopsi home industri anyaman bambu dengan menggunakan mesin dan dengan desain yang lebih canggih (komputasi). Lebih lanjut home industry kerajinan anyaman bambu desa Heuleut Leuwidinding Majalengka di era revolusi industri 4.0 akan mereduksi perekonomian pengrajin karena sebatas menghasilkan produk secara tradisional tanpa adanya pengembangan produk, hasil, dan pemasaran.